Trade and the environment : theory and evidence - Copeland, Brian Richard; Taylor, M. Scott (Michael Scott), 1960- (Princeton series in international economics., 2003)
"Nowhere has the divide between advocates and critics of globalization been more striking than in debates over free trade and the environment. And yet the literature on the subject is high on rhetoric and low on results. This book is the first to systematically investigate the subject using both economic theory and empirical analysis. Brian Copeland and Scott Taylor establish a powerful theoretical framework for examining the impact of international trade on local pollution levels, and use it to offer a uniquely integrated treatment of the links between economic growth, liberalized trade, and the environment. The results will surprise many." "Lucidly argued and authoritatively written, this book will provide students and researchers of international trade and environmental economics a more reliable way of thinking about this contentious issue, and the methodological tools with which to do so."--Jacket